S‐SAD phasing of monoclinic histidine kinase from Brucella abortus combining data from multiple crystals and orientations: an example of data‐collection strategy and a posteriori analysis of different data combinations. (1st July 2015) - Klinke, Sebastián; Foos, Nicolas; Rinaldi, Jimena J.; Paris, Gastón; Goldbaum, Fernando A.; Legrand, Pierre; Guimarães, Beatriz G.; Thompson, Andrew
<x xml:space="preserve">Abstract</x> The histidine kinase (HK) domain belonging to the light–oxygen–voltage histidine kinase (LOV‐HK) from Brucella abortus is a member of the HWE family, for which no structural information is available, and has low sequence identity (20%) to the closest HK present in the PDB. The `off‐edge' S‐SAD method in macromolecular X‐ray crystallography was used to solve the structure of the HK domain from LOV‐HK at low resolution from crystals in a low‐symmetry space group (P21) and with four copies in the asymmetric unit (∼108 kDa). Data were collected both from multiple crystals (diffraction limit varying from 2.90 to 3.25 Å) and from multiple orientations of the same crystal, using the κ‐geometry goniostat on SOLEIL beamline PROXIMA 1, to obtain `true redundancy'. Data from three different crystals were combined for structure determination. An optimized HK construct bearing a shorter cloning artifact yielded crystals that diffracted X‐rays to 2.51 Å resolution and that were used for final refinement of the model. Moreover, a thorough a posteriori analysis using several different combinations of data sets allowed us to investigate the impact of the data‐collection strategy on the success of the structure determination.